2022
DOI: 10.1177/10732748221076820
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Radiotherapy Localisation Computed Tomography-Based Radiomic Model for Predicting Survival in Patients With Nasopharyngeal Carcinoma Treated With Intensity-Modulated Radiotherapy Following Induction Chemotherapy

Abstract: Background Our purpose is to develop a model combining radiomic features of radiotherapy localisation computed tomography and clinical characteristics that can be used to estimate overall survival in patients with nasopharyngeal carcinoma treated with intensity-modulated radiotherapy following induction chemotherapy. Methods We recruited 145 patients with pathologically confirmed nasopharyngeal carcinoma between February 2012 and April 2015. In total, 851 radiomic features were extracted from radiotherapy loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Some studies reported on models constructed using radiomics features from the lymph nodes and briefly introduced the method for lymph node delineation in patients with NPC [ [21] , [22] , [23] , [24] , [27] , [28] , [29] , [30] , [31] , [32] ]. Xu et al [ 27 ] employed intra- and peritumoral MRI radiomics directly extracted from the largest metastatic lymph node to predict treatment response in patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported on models constructed using radiomics features from the lymph nodes and briefly introduced the method for lymph node delineation in patients with NPC [ [21] , [22] , [23] , [24] , [27] , [28] , [29] , [30] , [31] , [32] ]. Xu et al [ 27 ] employed intra- and peritumoral MRI radiomics directly extracted from the largest metastatic lymph node to predict treatment response in patients with NPC.…”
Section: Discussionmentioning
confidence: 99%